Quantitative Finance Stack Exchange is a question and answer site for finance professionals and academics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose I have two random variables, $X_1$ and $X_2$, that are independent (but not identically distributed) and assume both have hazard functions $\lambda_1(s)$ and $\lambda_2(s)$, for $s > 0$. Then how can I derive the hazard function of $\min(X_1, X_2)$?

EDIT: Let $S$ describe the lifetime of a person, then define $\theta_s(t) = P(S > s+t | S > s)$ as the survival function. Then define the hazard function as $\lambda(s) = \lim_{t \rightarrow 0} \frac{1}{t} (1-\theta_s(t)) = -\theta_s'(0)$

share|improve this question
Please define the term hazard function in the context that you are interested in. – Richard Apr 22 '14 at 7:26
Please see edit – siTTmo Apr 23 '14 at 15:40
up vote 4 down vote accepted

Note that $$P(X_i >s)= \exp\Big(-\int_0^s \lambda_i(u) du \Big),$$ for $i=1, 2$. Then, $$P(\min(X_1, X_2) >s) = P((X_1>s)\cap (X_2>s)) = P(X_1>s)P(X_2>s) = \exp\Big(-\int_0^s (\lambda_1(u)+\lambda_2(u)) du \Big).$$ That is, the hazard function for $\min(X_1, X_2)$ is $\lambda_1(s)+\lambda_2(s)$.

Alternatively, note that $$\lambda_i(s) = \lim_{\Delta s \rightarrow 0} \frac{P(X_i \leq s+\Delta s | X_i > s)}{\Delta s} \\ = \lim_{\Delta s \rightarrow 0} \frac{P(X_i > s) - P(X_i > s+\Delta s)}{\Delta s P( X_i > s)},$$ for $i=1, 2$. Then the hazard function of $\min(X_1, X_2)$ is given by $$ \lambda_{\min(X_1, X_2)}(s) = \lim_{\Delta s \rightarrow 0} \frac{P(\min(X_1, X_2) \leq s+\Delta s | \min(X_1, X_2) > s)}{\Delta s} \\ = \lim_{\Delta s \rightarrow 0} \frac{P(\min(X_1, X_2) > s) - P(\min(X_1, X_2) > s+\Delta s)}{\Delta s P( \min(X_1, X_2) > s)} \\ = \lim_{\Delta s \rightarrow 0} \frac{P(X_1 > s)P(X_2> s) - P(X_1 > s+\Delta s)P(X_2 > s+\Delta s)}{\Delta s P(X_1 > s)P(X_2> s)} \\ \small= \lim_{\Delta s \rightarrow 0} \frac{P(X_1 > s)P(X_2> s){\tiny-P(X_1 > s)P(X_2 > s+\Delta s) + P(X_1 > s)P(X_2 > s+\Delta s) }- P(X_1 > s+\Delta s)P(X_2 > s+\Delta s)}{\Delta s P(X_1 > s)P(X_2> s)} \\ \small=\lim_{\Delta s \rightarrow 0}\bigg(\frac{P(X_2> s)-P(X_2 > s+\Delta s)}{\Delta s P(X_2> s)} +\frac{P(X_2 > s+\Delta s)}{P(X_2> s)} \frac{P(X_1 > s)-P(X_1 > s+\Delta s)}{\Delta s P(X_1 > s)}\bigg) \\ = \lambda_1(s)+\lambda_2(s). $$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.